Visitor attachment to dolphins during an interaction programme, are there implications to dolphin behavior?. Issue 6 (12th July 2021) - Welsh, Thomas; Ward, Samantha
Abstract: Millions of people visit zoos and aquariums globally each year, with a smaller number choosing to participate in animal interaction programmes which allows visitors closer contact with individual animals. These are reportedly having mixed effects in increasing conservation‐related behaviors. Human‐animal interactions (HAIs) during these programmes are generally positive experiences for the human participants, however are there behavioral implications for the animals involved? The Bottlenose Dolphin ( Tursiops truncatus) is the most widely used cetacean for dolphin interactions, known as "swim with dolphin" (SWD) programmes. This study investigated visitor attachment to the dolphins they interacted with, whilst assessing behavioral implications of the dolphins. A total of 41 visitors to a Spanish dolphinarium, who participated in a SWD were surveyed using a modified version of the Lexington Attachment to Pets Scale. Alongside this, 15‐min continuous focal samples monitored three female dolphins (D1, D2, and D3) aged 22–40, split into pre ( n = 96), during ( n = 96) and post ( n = 96) SWD. 80% of visitors reported a sense of attachment to the dolphin they interacted with. An exploratory factor analysis extracted three factors from the survey, these were "relationships, " "emotional attachment, " and "non‐attachment." A Friedmans two‐way analysis of variance produced significant results for some behavior categories for each individual, including locomotory (D1: F 2 = 9.556, p < .01), rest (D2: F 2 = 14, p < .01, D3: F 2 = 10.889, p < .01) and individual play (D1: F 2 = 11.677, p < .01 D2: F 2 = 6.353, p < .05) however, pairwise comparison showed no differences pre‐post SWD. In this context it can be implied that participating in the SWD was neither enriching nor aversive for the individual animals, although due to the small sample size further research is required. As visitors reported a sense of attachment post HAI, this can have applications in improving conservation education during SWD. This study has provided scope for further research into methods that facilities can use to utilize the emotional attachment developed to individual animals to facilitate learning about conservation issues. Abstract : Figure 4: Visitor attachment and behavioural implications for dolphins participating in visitor interaction programmes. Research Highlights: Visitors formed a sense of emotional attachment to animals they interacted with. There were no welfare implications for the individual animals involved. Applications for improving conservation education output of animal encounters.